2014
DOI: 10.1002/14651858.cd009532.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral or parenteral iron supplementation to reduce deferral, iron deficiency and/or anaemia in blood donors

Abstract: BackgroundIron deficiency is a significant cause of deferral in people wishing to donate blood. If iron removed from the body through blood donation is not replaced, then donors may become iron deficient. All donors are screened at each visit for low haemoglobin (Hb) levels. However, some deferred blood donors do not return to donate. Deferred first-time donors are even less likely to return. Interventions that reduce the risk of provoking iron deficiency and anaemia in blood donors will therefore increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 53 publications
2
66
0
1
Order By: Relevance
“…3 Although both daily and intermittent supplementation can replete iron stores and increase hemoglobin levels, 4 iron supplements often cause gastric irritation, nausea, epigastric discomfort, and constipation, which may decrease compliance and long-term efficacy. 5 The absorption of iron supplements ranges from 2% to 13% and 5% to 28% in subjects with low iron stores 6 when consumed with and without food, respectively. Thus, a majority of the iron is unabsorbed.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although both daily and intermittent supplementation can replete iron stores and increase hemoglobin levels, 4 iron supplements often cause gastric irritation, nausea, epigastric discomfort, and constipation, which may decrease compliance and long-term efficacy. 5 The absorption of iron supplements ranges from 2% to 13% and 5% to 28% in subjects with low iron stores 6 when consumed with and without food, respectively. Thus, a majority of the iron is unabsorbed.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A number of studies have demonstrated that iron supplementation can reverse the iron depletion and reduce hemoglobin deferrals associated with blood donation. 3,4 Our group has recently documented that use of daily iron supplements is necessary for efficient recovery of donor hemoglobin and iron to support blood donation. 5 To date studies have separately assessed the effect of blood donation on iron stores, as assessed by serum or plasma ferritin, and hemoglobin, as assessed by venous hemoglobin concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 Iron supplements are required for iron replacement due to blood loss from a donation. [15][16][17][18] Thus, all donors in this study were given iron supplements after their blood donation. The difference in dose intake of each donor may be a factor that affects the ferritin level; however, ferritin itself was an acute phase reactant, 19,20 which may increase if donors were in or recently passed the inflammatory stage and the exact dose of iron supplements in each donor was not known.…”
Section: Discussionmentioning
confidence: 99%